Pergeseran Paradigmatik Problem Pikiran-Tubuh dalam Perdebatan Filosofis - Mukhtasar Syamsuddin (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2006)
The main purpose of this article is to describe in generaland briefly the paradigm alteration occurred in the philosophicaldebate of mind-body problem. This article is aimed at finding aclarification of certain causes based on the argumentations andsolutions offered by philosophers in facing mind-body problem. In this article, the purposed paradigm alteration is not onlyrelated to the ontological but also the epistemological andanalytical bases of mind-body problem. Such mind-body problem isnot only comprehended as a problem that requires a distinct statusbut also an explicit of both its character and its relati